Carbapenem Susceptibility Rate Against Gram-Positive and Gram-Negative Bacteria and Its Correlation with Consumption - George Arthur Mantiri; Rheza Paleva Uyanto; Meita Hendrianingtyas (Indonesian Association of Clinical Pathologist and Medical laboratory, 2024)
Antibiotic susceptibility is significant in patient management and needs close monitoring. This study aims to evaluate the Carbapenem susceptibility profiles and correlation between Carbapenem consumption and susceptibility of the most frequent isolates from blood, sputum, and urine in 2020–2022 from the non-intensive inpatients. The proportion of males and females was 54% and 46%, with the median age group of males and females both being 65-74 years. Higher Meropenem susceptibility was shown in urine isolates of female patients. Lower susceptibility to Meropenem was shown in 2021 compared to 2020 and 2022. Lower susceptibility was shown in isolates from sputum compared to blood and urine. The three-year susceptibility of Carbapenem was decreased compared to 3 years before. The susceptibility of E.coli and S.aureus to Meropenem showed relatively high proportions 95% and 88%, compared to K.pneumoniae (46%), A.baumanii (30%), P.aeruginosa (29%), and others. The susceptibility of isolates from non-intensive-care inpatients in 2020-2022 showed lower rates compared to the hospital-wide and the previous three years' rates. Meropenem consumption was highest compared to Imipenem with inhibitor and Doripenem. The susceptibility of Gram-negative rods to Meropenem showed higher proportions (58.9%) compared to Gram-positive cocci (26.2%). Carbapenem susceptibility was decreased, along with increased Carbapenem consumption but no significant statistical correlation between the susceptibility rates and the monthly defined daily dose.